2014
DOI: 10.4149/neo_2014_075
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR: a cancer-related long non-coding RNA

Abstract: Long non-coding RNA was dismissed as merely transcriptional "noise" in the past decades. Numerous researches have shown that lncRNAs regulated gene expression at the epigenetic level. Moreover, lncRNAs played important roles in proliferation, apoptosis and invasiveness of tumor cells, and participated in metastatic capacity of cancers. Recent studies revealed HOX transcript antisense RNA, a lncRNA with regulatory functions of transcription, could bind PRC2 and LSD1/CoREST/REST complexes and direct to the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 78 publications
1
128
0
1
Order By: Relevance
“…HOTAIR was first identified as one of 231 lncRNAs that are associated with the human HOX loci, which binds to polycomb repressive complex 2 (PRC2), a transcriptional co-repressor, and recruits it to silence the target genes (18). HOTAIR is also able to interact with a second histone A B modification complex, the LSD1/CoREST/REST complex, which functions by coordinating the targeting of PRC2 and LSD1 to chromatin for methylation of coupled histone H3K27 and demethylation of K4 (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOTAIR was first identified as one of 231 lncRNAs that are associated with the human HOX loci, which binds to polycomb repressive complex 2 (PRC2), a transcriptional co-repressor, and recruits it to silence the target genes (18). HOTAIR is also able to interact with a second histone A B modification complex, the LSD1/CoREST/REST complex, which functions by coordinating the targeting of PRC2 and LSD1 to chromatin for methylation of coupled histone H3K27 and demethylation of K4 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified the aberrant expression of HOTAIR in a number of cancer types, including breast, colon, bladder, renal, pancreatic, cervical and lung cancer, and a high level of HOTAIR expression has been correlated with enhanced breast, colon and gastric cancer metastasis. In addition, HOTAIR-knockdown is able to inhibit the invasion and proliferation of cells, as well as altering cell cycle progression and inducing cells apoptosis, thus indicating that HOTAIR may function in the modulation of cancer progression (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a few lncRNAs have been reported to be related to the progression of human cancer [35, 36]. Several lncRNAs have been shown to serve as prognostic and diagnostic markers, such as HOTAIR for brain, breast, and colon cancer [37-40]; MALAT-1 for liver, breast, lung, and prostate cancer [41-43]; OOC1 for colon cancer; and SChLAP1, PCA3, and PCAT-1 for prostate cancer [44, 45]. Moreover, growing evidence has further indicated that lncRNAs functionally act as suppressors of oncogenes.…”
Section: Introductionmentioning
confidence: 99%
“…The 5' domain of HOTAIR can bind to PRC2, while the 3' domain of HOTAIR can bind to the LSD1 (lysine specific demethylase 1)/ CoREST (Co-repressor of RE1-silencing transcription factor)/REST complex; after that, the complexes are targeted and assembled to the HOXD locus; and coordinately regulate histone H3K27 methylation and histone histone 3 methylated at lysine 4 demethylation; consequently, the transcription across 40 kb of the HOXD locus is silenced in trans by DNA methylation [106] . These indicate that the HOTAIR-induced assembly and targeting of LSD1 and PRC2 complexes is a general mechanism for gene silencing across the genome, which plays a vital role in the association with invasion and metastasis in HCC [64] . Expression of HOTAIR is also associated with tumor size and lymph node metastasis in HCC patients [62] .…”
Section: Hox Transcript Antisense Rnamentioning
confidence: 99%